2015
DOI: 10.1007/s11229-014-0615-y
|View full text |Cite
|
Sign up to set email alerts
|

At least not false, at most possible: between truth and assertibility of superlative quantifiers

Abstract: Generalized Quantifier Theory defines superlative quantifiers at most n and at least n as truth-conditionally equivalent to comparative quantifiers fewer than n+1 and more than n−1. It has been demonstrated, however, that this standard theory cannot account for various linguistic differences between these two types of quantifiers. In this paper I discuss how the distinction between assertibility and truth-conditions can be applied to explain this phenomenon. I draw a parallel between the assertibility of disju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
(55 reference statements)
1
7
0
Order By: Relevance
“…After having excluded potential confounding effects of the unroundness of the numbers used in the experimental items, we take the processing cost incurred in these specific regions to be associated with the derivation of an ignorance implicature, similarly to the interpretation of similar findings by studies on scalar implicatures using the same paradigm (Breheny et al 2006;Panizza et al 2009). Our online finding is in line with the neo-Gricean pragmatic accounts that derive ignorance as a scalar implicature, but again at odds with Geurts & Nouwen (2007); Nouwen (2010); Coppock & Brochhagen (2013b); Spychalska (2015), who would predict the opposite effect, assuming that the contradiction between the speaker's epistemic state as encoded in the semantics of at least or signalled by its use and of that revealed by the +knowl-edgeability contexts would cause extra processing cost. As to the secondary goal of our study, we found no evidence that the ignorance reading that arises when at least is embedded under a universal modal is due to the wide-scope movement of at least.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…After having excluded potential confounding effects of the unroundness of the numbers used in the experimental items, we take the processing cost incurred in these specific regions to be associated with the derivation of an ignorance implicature, similarly to the interpretation of similar findings by studies on scalar implicatures using the same paradigm (Breheny et al 2006;Panizza et al 2009). Our online finding is in line with the neo-Gricean pragmatic accounts that derive ignorance as a scalar implicature, but again at odds with Geurts & Nouwen (2007); Nouwen (2010); Coppock & Brochhagen (2013b); Spychalska (2015), who would predict the opposite effect, assuming that the contradiction between the speaker's epistemic state as encoded in the semantics of at least or signalled by its use and of that revealed by the +knowl-edgeability contexts would cause extra processing cost. As to the secondary goal of our study, we found no evidence that the ignorance reading that arises when at least is embedded under a universal modal is due to the wide-scope movement of at least.…”
Section: Resultssupporting
confidence: 86%
“…The higher coherence rates in the case of the -knowledgeability contexts as opposed to +knowledgeability contexts go against Geurts & Nouwen's (2007), Nouwen's (2010), Coppock & Brochhagen's (2013b), and Spychalska's (2015) accounts. That is, those accounts by virtue of a semantic encoding -in one way or another -of the epistemic component of at least predict that the target sentence with at least should be judged as more compatible with a preceding -knowledgeability context than with a +knowledgeability context.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations